Digital skills requirements of the Real Estate, Finance and Business Services sector in South Africa - Civilcharran, S.; Maharaj, M. S. (South African Journal of Higher Education, 2023)
Purpose: Owing to the digital skills shortage in South Africa, this article ascertains the digital skills requirements of the Real Estate, Finance and Business Services sector in South Africa. The aim of this study is to understand which digital skills graduates are expected to possess when they enter this sector, as well as its level of importance of each digital skill. The Real Estate, Finance and Business Services sector has been South Africa’s largest GDP contributor for the past several years, therefore this particular sector was selected for this study. Methodology: A quantitative research approach was undertaken to survey 387 business professionals from the Real-Estate, Finance and Business Services sector in South Africa. The survey was conducted online via LinkedIn and participants acted in their individual capacity as business professionals, resulting in a response rate of 49 per cent. Findings: Digital skills related to the use of software applications and Web tools, the use of information systems, and the application of security measures in digital environments were analysed using Principal Component Analysis. The findings revealed that this industry sector placed a great deal of importance on a graduate’s ability to apply security measures in digital environments, particularly pertaining to Personal IT Security Skills. Originality: This study will greatly assist South African higher education institutions with regard to curriculum development in the commerce disciplines, since most commerce students feed into the said sector. A curriculum that is better aligned to meet industry needs, will ensure that graduates are adequately prepared for this particular South African industry sector. A study of this nature is lacking in the South African context, which will greatly help South African higher education institutions to align their curricula to meet this sector’s digital skills need.